Thermal Properties and Cooling Simulation of Red Dragon Fruit Using the Finite Difference Method - Maghfiroh, Lailatul; Sumarlan, Sumardi Hadi; Hammam, Hammam (Journal of Applied Agricultural Science and Technology, 2025)
Red dragon fruit (Hylocereus polyrhizus) can be transformed into various processed products, such as chips, jam, and juice. However, thermal processing may significantly alter its physical and chemical properties. As the calorific properties vary among different fruits, this study aims to measure the thermal properties of red dragon fruit. By measuring its thermal properties, red dragon fruit can be processed with improved energy efficiency and optimized thermal management. This study aims to examine the thermal properties and perform a cooling simulation of red dragon fruit. The cooling simulation, based on one-dimensional radial thermal flow, was conducted using the spherical heat equation explicitly discretized by the Forward Time Central Space (FTCS) scheme within the Finite Difference Method (FDM). The specific heat, thermal diffusivity, and thermal conductivity of red dragon fruit were 3.827 kJ/kg oC, 9.18 x 10-4 cm2/s, and 0.34 W/m oC, respectively. The overall average coefficient of determination (R2) from the validation test of the simulation results was 0.9654.  Based on these findings, the one-dimensional (radial) discretized heat transfer equation model can be used to predict the temperature distribution in spherical fruit over time, based on its thermal diffusivity. However, this approach has limitations. Future research would benefit from measuring the thermal diffusivity of whole red dragon fruit and applying a three-dimensional discretized heat transfer equation to obtain more accurate results and minimize potential errors.